Dukungan Keluarga Terhadap Peningkatan Kualitas Hidup Lansia Melalui Pendekatan "Bahaum Bapakat" - Sari, Magdalena Meda; Desi, Desi Desi; Dese, Dennys Christovel (Jurnal Keperawatan Muhammadiyah, 2021)
Abstrak Background: Elderly is someone who has reached the age of 60 years and over and has experienced physical deterioration. Changes experienced in the aging process can have a negative impact or cause problems for the elderly such as feeling helpless and useless, feeling hopeless about the life they are living, feeling inferior so that the elderly isolate themselves and avoid their environment.. The aging process can have an impact on the quality of life. The quality of a person's life can be influenced by environmental aspects, physical aspects, mental aspects and social aspects. If all aspects can be fulfilled by the elderly, the quality of life they get is also good. Family support has a good function in improving the quality of life of the elderly, because family plays an important role in the social support closest to the family. Purpose: This study aims to describe family support for improving the quality of life of the elderly through the traditional "bahaum bapakat" approach. Methods: the study used a qualitative method by conducting semi-structured interviews, participants who contributed as many as 10 elderly people and were taken by purposive sampling, data was collected through audio recorders and interview guides which were analyzed with the stages of data collection, coding, selecting useful data for determination. themes, then data triangulation was carried out. Results: Environment as a support system for the quality of life of the elderly, Physical health care for the elderly in Sungai Buluh Village, Emotion, Spirituality, and Self-description of the elderly in Sungai Buluh Village, Social interaction, Family Support System, Social role: bahaum elderly in Sungai Buluh Village. Conclusion: Family support through the approach bahaum bapakat has an influence on improving the quality of life of the elderly in Sungai Buluh Village.Keywords: the elderly, the quality of life, family support, bahaum bapakat